Thermodynamic Characterization of DNA with 3-Deazaadenine and 3-Methyl-3-Deazaadenine Substitutions: The Effect of Placing a Hydrophobic Group in the Minor Groove of DNA - Ganguly, Manjori (2010)
In many high-resolution structures of DNA there are ordered waters associated with the floor of the minor groove and extending outward in several layers. It is thought that this hydration structure, along with cations, reduces the Coulombic repulsion of the interstrand phosphates. In previous studies, the replacement of the 3-N atom of adenine with a C-H to afford 3-deazaadenine was shown to decrease the thermodynamic stability of DNA via a reduction in the enthalpic term. Using spectroscopic and calorimetric methods, we report herein a rigorous examination of the thermodynamics of DNA with 3-deazaadenine modifications, and report for the first time how the presence of a minor groove methyl group, i.e., 3-methyl-3-deazaadeine, affects DNA stability, hydration and cation binding. The methylation of adenine at the N3-position to yield N3-methyladenine represents an important reaction in the toxicity of many anticancer compounds. This minor groove lesion is unstable and cannot be readily studied in terms of its effect on DNA stability or structure. Our studies show that 3-methyl-3-deazaadenine, an isostere of N3-methyladenine, significantly destabilizes DNA (ΔΔG > 4 kcal•mol(−1)) due to a significant drop in the enthalpy (ΔH) term, which is associated with a lower hydration of the duplex relative to the unfolded state.